A socio-enviromental history of commercial tobacco farming in Southern Rhodesia and Zimbabwe, c.1893-2000s - Doro, Elijah (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.